Nutritional content and amino acid profile of juleh: Balinese traditional food fermentation - Puryana, I Gusti Putu Sudita; Antarini, Anak Agung Nanak (International journal of health sciences, 2018)
Juleh was a typical food in Sibetan Karangasem Bali area made from koro beans which boiling and soaking process for four days. It was then fermented naturally for one day without using special bacteria. Juleh was consumed by fried or fermented for a day then mixed with the Balinese spices further stir fried or made a soup. The study was intended to determine the nutrients content, the amino acid composition in Juleh. The results showed that the nutrient content of fried Juleh was higher than fermented, with protein content 50,23%, fat content 14,94%, and carbohydrate content 28,24%. Juleh fermentation contains 15 types of the amino acids that were dominated by the glutamic acid that causes Juleh taste to be tasty. The amino acid content in fermentation Juleh was higher than all types of the amino acids, both essential and nonessential, rather than amino acid content in Seredele.